Analisis Perbandingan Persepsi Kualitas Pelayanan Dan Kepuasan Konsumen Jasa Transportasi Online Di Sumatera Selatan - PUTRI, NYAYU KHAIRANI (Akuntansi dan Manajemen, 2020)
The purpose of this research is to compare perceptions of service quality and consumer satisfaction of online transportation services in South Sumatra, with a Case Study of Go-Jek Consumers, Go-Ride Service Users and Grab Consumers, Grabbike Service Users. This research is a comparative study. Information about the research is obtained from data collection techniques that have been carried out on research subjects, namely users of Go-Jek (GoRide) and Grab (Grabbike). The population in this study ware people who had used Go-Jek and Grab, while the study sample was 100 respondents. The Paired Sample T-Test is a data analysis technique in this study using the IBM SPSS Statistics 22 application.The results showed that there was no significant difference between Go-Ride Service Quality and Grabbike Service Quality, and there was a significant difference between Go-Ride Consumer Satisfaction and Grabbike Consumer Satisfaction.